Investigation of the Relationship between Empathic Anger and Violence Tendency in Nurses - Fadime Ulupınar; Yasemin Erden; Nurgül Karakurt; Şeyda Karasu (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: While empathy is generally regarded as a positive trait, the emergence of empathic anger among nurses can have adverse effects on their mental well-being and, more importantly, on their tendency for violence.Aim: The aim of the study was to determine the relationship between empathic anger and violence tendencies in nurses.Method: This cross-sectional study was conducted on 348 nurses who agreed to participate in the research working in a hospital in Erzurum. The study data were collected with a personal information form, empathic anger scale, and violence tendency scale. The data analyzed using One-Way ANOVA and independent samples t-tests, and Hierarchical regression analyses.Results: It was found that the mean Emphatic Anger Scale score of the nurses included in the study was 23.20 ± 5.66, and the Violence Tendencies Scale score was 44.35 ± 11.01. It was found that there was a positive, statistically significant relationship between the Emphatic Anger Scale scores and Violence Tendencies Scale mean scores of the nurses (p lt; 0.001). In the regression model, Emphatic Anger Scale scores were entered as the sole predictor, explaining 9.6% of the variance in violence tendency (R² = 0.096, Adj. R² = 0.093, p lt; 0.05).Conclusion: As a result, it shows that empathic anger in nurses has a significant and positive effect on violent tendencies. In addition, it was determined that as the empathic anger levels of the nurses increased, their level of violence tendencies also increased.